Impact of Protein Supplementation and Presumptive Treatment for Enteric Pathogens on Infant Growth from 6–12 Months of Age: Results of a Cluster-Randomized Controlled Trial. (29th May 2020) - Palmer, Amanda; Ali, Hasmot; Hossain, Md Iqbal; Pasqualino, Monica; Ayesha, Kaniz; Shaikh, Saijuddin; Haque, Rezwanul; Islam, Md Tanvir; Schuh, Holly; Hasan, Khaled; Dyer, Brian; Johura, Fatema-Tuz; et al.
Abstract: Objectives: Intake of high-quality protein may be insufficient to support growth in the context of high enteric pathogen carriage and environmental enteric dysfunction. Our objective was to test whether supplemental protein, with or without presumptive treatment for enteric pathogens, would improve infant growth from 6–12 months of age. Methods: We conducted a 2 × 4 factorial cluster-randomized trial in rural Bangladesh. The first factor was azithromycin treatment (10 mg/kg * 3 days) or placebo at 6 & 9 months of age. The second factor, delivered from 6–12 months of age, consisted of: supplemental protein as daily porridge (125 kcal/d, with 10 g protein/day as egg white powder) or a daily egg; an isocaloric daily porridge; or nutrition education alone. The present aim tested the impact of the protein-rich porridge, with or without azithromycin treatment. All infants born in the study area over a 9-mo period were eligible and consented at ∼3 mo of age. Trained field workers measured infant size at 6, 9, and 12 mo of age using standardized protocols. We used linear regression with generalized estimating equations to test the interventions' impact on anthropometric indices, respectively, at 12 mo of age, controlling for baseline measures. Analysis was intention-to-treat. Results: Overall, 2205 infants were enrolled from 282 clusters and exposed to both nutrition (1074 in protein arm from 140 clusters; 1074 in the isocaloric arm from 142 clusters) and presumptive treatment interventions. At baseline, 18.7%, 16.9%, and 6.4% of infants were stunted, underweight, and wasted, respectively. There was no statistical interaction between protein supplementation and azithromycin treatment for any of the anthropometric indices, so groups were combined. In the analysis of main effects, added protein had no impact on mean length-for-age (β = 0.01; 95% CI: −0.06, 0.08), weight-for-age (β = −0.002; 95% CI: −0.06, 0.05), or weight-for-length (β = −0.04; 95% CI: −0.12, 0.05) Z-scores at 12 mo of age. Conclusions: Supplemental protein from 6–12 mo of age had no effect on mean linear or ponderal growth measured at 12 mo of age, irrespective of presumptive treatment for enteric pathogens with azithromycin. Funding Sources: The Bill and Melinda Gates Foundation.